Emerging Finnish Adults Coping with Cancer: Religious, Spiritual, and Secular Meanings of the Experience - Saarelainen, Suvi-Maria (Pastoral psychology, 2017)
The article presents empirical findings on religious, spiritual, and secular coping among emerging Finnish adults with cancer and seeks an understanding of the different meanings they constructed of their experience with cancer. Autobiographical interviews and life tree drawings of 16 emerging adults were analyzed utilizing a narrative approach. To gain a deeper understanding of the cancer-coping and meaning-making processes, the stories of Beth, Sophia, and Anna are explored in detail. An exploration of the meaning-making process of all the participants shows that over time many of the participants were able to find meaning in their cancer experience. Religious meaning was found when the disease was discovered as a calling from God, spiritual meaning was discovered within a buffered identity and important relationships, and secular meaning was found in the courage to make a career change. The theoretical discussion points out a gap between the disciplines of theology and psychology of religion. The gap is partly bridged by utilizing the concepts of lived religion and existentially oriented spirituality in the discussion of meaning-making theories.